A Mechanism-Centred Approach to Evaluating Complex Aid Interventions: The Case of Accompanying Measures to Budget Support - Johannes Schmitt; Franziska Krisch (Journal of MultiDisciplinary Evaluation)
Background: Current methodological debates related to theory-based evaluations (TBE) centre around questions how to improve the explanatory strength of these approaches and how to integrate mechanisms as analytic concept. Particularly in complex aid interventions, when multiple elements are expected to interact and thus create an added value, exploring mechanisms as an analytical tool can be promising.